From the Altar to the Household. The Challenging Popularization of Christian Devotional Images, Objects, and Symbols in 16th and 17th Century China - de Caro, Antonio (Eikón / Imago, 2022)
After the expeditions of wealthy merchants and Franciscan missionaries during the 14th century, the Chinese empire under Ming rule did not engage profusely with the European world, and vice versa. This period of artistic and intellectual silence and detachment was broken in the late 16th century when the Jesuit missionaries reconnected two worlds –Europe and China– reactivating previous medieval commercial, artistic, and intellectual routes. Silk –the product par excellence commercialized along the routes connecting China and Europe– was then accompanied by other precious products, including Chinese ceramics reaching various European courts and European paintings that reached the Ming court in Beijing. This paper addresses the complex and challenging popularization of Roman Catholicism through objects and images during the early modern era. In particular, it focuses on the diffusion of devotional images and objects used by Roman Catholic missionaries and the religious practices related to them.